CP-016 Analysis of antibiotic prescriptions for surgical prophylaxis in patients with upper and lower extremity injuries at the paediatric surgery clinic. (14th February 2016) - Sviestina, I; Mozgis, J; Mozgis, D
Abstract : Background: There are numerous audits performed in order to evaluate the appropriateness of the use of antibiotics (AB) in surgical prophylaxis in adult populations, but there is still a shortage of data regarding paediatric surgery. Purpose: To analyse prescribed AB and AB doses to patients with upper and lower extremity injuries before and after introduction of hospital recommendations for surgical prophylaxis (HR) at the paediatric surgery clinic (PSC) and to evaluate the usefulness of the AB electronic prescription form. Material and methods: Retrospective study. Patients aged <18 years hospitalised at the PSC were included in the study. Study period: 2011–2014. All data on patients were obtained from the patients' medical records (2011–2013), as well as from the hospital software (2014). The HR (accepted in September 2013) and the summary of the product characteristic (SPC) were used as information resources for analysis of dosing errors. The cefazolin dose in the HR was 25 mg/kg but in SPC it was 25–50 mg/kg. AB prescriptions were analysed before the introduction of the HR (201–013) and after (2014). Results: 743 (66%) patients had AB prophylaxis in 201–013. In 2014, there were 367 electronically filled AB prescription forms. 546 (73%) patients had the correct duration of AB prophylaxis (1 dose) in 201–013 but in 2014, 254 (69%) patients. In 2011–2013, AB choice (cefazolin) was correct in 377 (51%) cases compared with 361 (98%) cases in 2014. In 2011–2013, AB doses were wrong in 217 (59%) prescriptions according to HR compared with 268 (74%) prescriptions in 2014. According to SPC, AB doses were wrong in 120 (33%) prescriptions in 2011–2013 and in 34 (9%) prescriptions in 2014. Conclusion: Although the guidelines were discussed and accepted by surgeons only a few positive trends (eg, the correct AB choice) were observed with AB treatment guidelines not having a major impact on AB use. The electronic AB prescription form did not improve the situation either. There is a need for new ways of promoting adherence to guidelines and appropriate antibiotic use. References and/or Acknowledgements: Ciofi Degli Atti M, et al . Eur J Clin Pharmacol 2015;71:483-8 Formaini N, et al . J Pediatr Orthop 2012;32:737-40 No conflict of interest.